The ghost dance religion of 1890 and the Mormons : a study of comparisons - Alston, Booker T (Department of Religious Studies, 2014)
The goal of this study is to examine the historical circumstances and individuals involved in this narrative as a way to critically reflect on the use of comparison in the production, circulation, and perpetuation of knowledge about religion.